Trends in the Female Longevity Advantage of 19th-Century Birth Cohorts: Exploring the Role of Place and Fertility - Jason M. Fletcher; Michael Topping; Won-tak Joo (Institute of Labor Economics (IZA), 2023)
This paper uses massive online genealogy data from the United States over the 19th century to estimate period and cohort-based sex differences in longevity. Following previous work, we find a longevity reversal in the mid-19th century that expanded rapidly for at least a half century. For measures of conditional survival past childbearing age, females enjoyed a longevity advantage for the whole century. Unlike most mortality databases of this period, genealogical data allows analysis of spatial patterns and of the impacts of fertility on longevity. Our results suggest very limited evidence of spatial (state) variation in these patterns. We do, however, find evidence that the associations between fertility and longevity partially explain the trends.
Keywords: J11; 330; longevity; sex differences; US; genealogy